Techniki kontrolowania prawidłowości spływu należności - Michalski, Grzegorz (Accounts Receivable Monitoring Techniques, 2005)
The maximization of wealth of its owners is the basic financial aim in the management of the enterprise. Accounts receivable management contributes to the realization of this aim. The article presents the methods of monitoring accounts receivable accessible for enterprises.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 33-42